Towards A Better Understanding of Good Faith Concept in Islamic Contract Law - Beom, Choi, Seok; Hyeon, Han, Nag; Khan, Muhammad; Han, Bae, Jung (International Journal of Engineering and Technology, 2018)
The purpose of this article is to clarify the concept of the duty in good faith in Islamic contract law. The principle of good faith is vital in contract law which covers the contract period ranging from pre-contractual stage of the contract to conclusion of the contract. In agreement the contractual parties would come across some pledges, such as the commitment to perform with the good faith obligation, stipulation of the required information, negotiation process’s transparency, promise to cooperate and commitment not to diverge from contract and if these commitments are not fulfilled, the defaulting party has to pay some performance bonds, such as the commitment to negotiate, the duty to disclose, paying reparation for loss of position of the contract and benefit, contract’s termination during the implementation phase due to the errors in the pre-contract phase. Good faith is applying to the world legal systems, which lead to the development of international law. For that reason, the elements of good faith in the civil law, the common law, international law and Islamic law are described in the following part to provide an attention for the study of good faith in more detailed. However, the main focus of the article to explores the Islamic contract law approach for this matter. Descriptive and analytical research methodology has adopted in this study in which relevant materials (verses) have been collected from the Quran, Islamic books, related research papers and web sites.